An Old Betrayal - Finch, Charles (Charles B.) (Finch, Charles (Charles B.) Charles Lenox series., 2013)
"On a spring morning in London, 1875, Charles Lenox agrees to take time away from his busy schedule as a Member of Parliament to meet an old client at Charing Cross. But when their cryptic encounter seems to lead, days later, to the murder of an innocuous country squire, this fast favor draws Lenox inexorably back into his old profession. Soon he realizes that, far from concluding the murderer's business, this body is only the first step in a cruel plan, many years in the plotting. Where will he strike next? The answer, Lenox learns with slowly dawning horror, may be at the very heart of England's monarchy. Ranging from the slums of London to the city's corridors of power, the newest Charles Lenox novel bears all of this series' customary wit, charm, and trickery--a compulsive escape to a different time"--